Carbon Nanotubes: A New Weapon In Health Care Treatment - SAROJINI S; RAJASEKAR S; KOUMARAVELOU K (International Journal of Pharma and Bio Sciences, 2010)
Carbon nanotubes (CNTs) are considered to be one of the innovative resources in nanotechnology with possible use in wide range of biomedical application viz. cancer treatment, bioengineering, cardiac autonomic regulation, platelet activation and tissue regeneration. The effect of CNTs on cells and tissues are extremely important for their use in various complex biological systems. However their utility is limited due to the problems faced during their delivery to target sites. Research is under the way to explore a novel technique to deliver the therapeutic system, for use in various diseases. This tutorial review briefs the current state of knowledge in the interdisciplinary field of CNT based nano-biotechnology application towards therapeutics.